Analisis Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Belanja Daerah di Pulau Madura - Bernike Trivena Noveliana; Mulyanto Nugroho (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
It is used to known how balancing funds and original local goverment revenue are impact to regional expense in 2019-2023. The population was taken from four districts on Madura Island. The budget realization report for each district is the secondary data used. Use SPSS program with linear regression analyze. The result is that original local goverment revenue, revenue sharing fund, and specific allocation fund didn't impact to regional spending. Apart from that, general allocation funds is impact to regional expense. And all of them are significant impact on regional expense in four districts on Madura Island simultaneously.